2008
DOI: 10.1016/j.jcf.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between practice patterns and body mass index percentile in infants and young children with cystic fibrosis

Abstract: Treating infants less than two years old with dornase alpha may improve nutritional outcome through age six.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A better nutritional status was indeed linked to the prescription of dornase alpha (Pulmozyme ®) under the age of 2 years (Padman et al, 2008), whereas the effects of Pulmozyme in this age group have only been reported in one limited study (Berge et al, 2003) where 9 infants were given the drug for 2 weeks. The necessity to conceive and study new strategies stems from the fact that current ones are relatively powerless in preventing pulmonary lesions in early diagnosed infants (Stick et al, 2009).…”
Section: Marked Differences In Clinical Results Between Cf Centres: Why?mentioning
confidence: 99%
“…A better nutritional status was indeed linked to the prescription of dornase alpha (Pulmozyme ®) under the age of 2 years (Padman et al, 2008), whereas the effects of Pulmozyme in this age group have only been reported in one limited study (Berge et al, 2003) where 9 infants were given the drug for 2 weeks. The necessity to conceive and study new strategies stems from the fact that current ones are relatively powerless in preventing pulmonary lesions in early diagnosed infants (Stick et al, 2009).…”
Section: Marked Differences In Clinical Results Between Cf Centres: Why?mentioning
confidence: 99%
“…For centers with higher overall FEV 1 PP, patients with higher FEV 1 PP had on average more clinic visits, more intensive monitoring, S48 | and more aggressive treatment. 80,81 those with higher lung function were less likely to receive treatment. 82 Further analysis of ESCF data has recently demonstrated that following an acute decline in FEV 1 , antibiotic treatment, especially in-patient, is associated with a greater likelihood of recovery of that loss, even in patients with high lung function.…”
Section: Contributions Of the Registry To Clinical Carementioning
confidence: 98%
“…Using data from the ESCF registry, two studies examined differences between center practices based on median FEV 1 PP. For centers with higher overall FEV 1 PP, patients with higher FEV 1 PP had on average more clinic visits, more intensive monitoring, and more aggressive treatment . However, recent studies show that decreases in lung function are not always followed by treatment interventions.…”
Section: Contributions Of the Registry To Clinical Carementioning
confidence: 99%
“…All of the preceding studies collectively suggest early intervention in nutrition and initiation of pulmonary therapies as a means of prolonging lung remodeling and addressing failure to thrive. In a retrospective cohort study of CF registry data (1993-2004) from three CF centers, Padman et al [44] compared initial management with respiratory, antimicrobial, and nutritional agents in infants. They examined the association between dornase alfa use prior to two years of age and body mass index (BMI) percentile over time, controlling for possible factors including genes, gender, race, CF center, presentation, age at diagnosis, sweat value, delta-F508 status, first P. aeruginosa infection, second-year weight percentile, supplemental feeding use, and pancreatic enzyme use.…”
Section: Benefits Of Early Screening and Diagnosismentioning
confidence: 99%